Alginate: Current Use and Future Perspectives in Pharmaceutical and Biomedical Applications - Marta Szekalska; Agata Puciłowska; Emilia Szymańska; Patrycja Ciosek; Katarzyna Winnicka (International Journal of Polymer Science)
Over the last decades, alginates, natural multifunctional polymers, have increasingly drawn attention as attractive compounds in the biomedical and pharmaceutical fields due to their unique physicochemical properties and versatile biological activities. The focus of the paper is to describe biological and pharmacological activity of alginates and to discuss the present use and future possibilities of alginates as a tool in drug formulation. The recent technological advancements with using alginates, issues related to alginates suitability as matrix for three-dimensional tissue cultures, adjuvants of antibiotics, and antiviral agents in cell transplantation in diabetes or neurodegenerative diseases treatment, and an update on the antimicrobial and antiviral therapy of the alginate based drugs are also highlighted.